Professional status of executive coaching: a study of the South African market - Masiza, Hlonipha Nobuntu (My University, 2017)
The study occurs against a backdrop of the growth of the coaching industry globally as it increases in popularity (Linley, 2006; Filley-Travis & Lane, 2006) particularly in organizational settings, where coaching is increasingly being relied upon as a significant part of learning and development (Joo, 2005). Despite the exponential growth, there is still no recognition of professional status by the state and society at large in the way that other professions are recognised. In 2008 the global coaching convention resolved to explore the feasibility of professionalisation in the different markets. Locating this global discussion on professionalization of coaching in the South African market, this study was conducted to establish the status of this market and to provide an understanding of the factors underlying the professionalization of coaching in South Africa and their respective contribution to the status quo. The study approaches the developments from several perspectives including the sociology of the professions and stakeholder theory. Taking a qualitative research methodology approach, data was obtained from semi-structured interviews with stakeholders and archival data including policies, legislation and websites. The Burrage multi-actor framework (Burrage, Jaraush, & Siegrist, 1990) was used as a guideline for sampling in order to provide a multiple stakeholder perspective. There were different discussion guides for the different stakeholder groupings. In total, there were fourteen interviews conducted. Data was analysed using Atlas software. Findings of the study reveal that the developments in the South African executive coaching industry have not followed the path of traditional professions as described by Willensky (1964). The prevailing position reflects a mixture of traditional and modern characteristics of professionalisation. To a large extent, there was consensus on the issues that are common across all stakeholder groupings, although there was some dissent as these stakeholder groupings have varying motives and positions. There was greater divergence of view within professional associations as a single stakeholder group. Part of this is reflected in the disparate occupational strategies pursued.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (Business and Executive Coaching). Wits Business School Johannesburg, 2017
Keywords: Executive coaching--South Africa